Disgrafía motriz y la iniciación de la escritura en los niños de inicial del CECIB “Luís Plutarco Cevallos Guerra” cantón Alausí, provincia de Chimborazo, comunidad Ozogoche alto período académico 2020-2021 - Chucuri Pilataxi, Rosendo (2021)
Motor dysgraphia is a learning difficulty that makes it impossible to write correctly, disturbing writing in both form and meaning, hindering the normal development of the teaching-learning process. The present study aims to determine the relationship of dysgraphia in the initiation of the writing of students of initial education of the CECIB “Luis Plutarco Cevallos”. The research is a basic, quantitative-qualitative approach with a non-experimental design and descriptive-correlational field study. Two instruments were used for data collection: the survey and direct observation of the students. The teaching of manual writing is essential for proper learning, this ability develops as schooling progresses and goes through three stages: A high school, the child acquires the graphomotor control necessary for subsequent writing: the calligraphic phase, teaching is focused on the writing of different graphics of the letters and their sequencing, and the last stage of improvement when a child consolidates the acquired learning, he can personalize it and give his style. It is concluded that the main problem is that children have illegible handwriting or dysgraphia, the important is a correct application of technical methods in the development of fine motor skills, to prevent this problem from an early age. The results show several causes of dysgraphia, reflected in the quality of writing, aspects to be corrected to improve the learning process.